Tree-pulling experiment : an analysis into the mechanical stability of rain trees - Harnas, F. R. (2011)
Tree-pulling experiments were conducted in Singapore involving 20 rain trees (Samanea saman) growing in four different soil types (1) structural soil with 80% granite chips and 20% sandy loam soil, (2) structural soil with 50% granite chips and 50% sandy loam soil, (3) in situ soil and (4) top soil. The trees were pulled over with a winch attached to the stem at a standard height of 1.3 m and the force required to uproot or break the trees were recorded. The physical above and below ground characteristics of the trees were also measured. All 20 trees in this study failed via uprooting without any stem fracture. Analysis of the data showed that the maximum resistive bending moment (BMmax) was positively correlated with the overall size of the root plate, the size (diameter) of the individual roots and the extent of crown spread. The dry mass of crown was significantly greater in the 80:20 structural soil treatment while no significant difference was found between the other soil types. The trunk diameter was not significantly different between treatments. Significant differences were observed in the depth of root plates where those grown in top soil had significantly deeper root plates as opposed to the other treatments but though deeper, the vast majority of trees planted in top soil exhibited fibrous rather than structural roots. The cross-sectional area of roots which is indicative of the size of the individual roots showed a significantly greater value in the 80:20 structural treatment while the 50:50 structural and top soil treatments had the lowest values. Significant differences in BMmax were only observed in the in situ soil type while the rest of the planting substrates exhibited values that were comparable and not significantly different.